A new proposal for a statistically-derived biogeographical regionalization of Algeria, North Africa - Tahri, Djilali; Meddour, Rachid; Chatelain, Cyrille; Médail, Frédéric (Mediterranean Botany, 2026)
Most proposals relating to the biogeographic regionalization of Algeria have been made by traditional qualitative method (geography, geology, climatology, vascular flora), on the basis of expert’s opinions. A new biogeographic regionalization of Algeria is herein proposed, based on quantitative approach and using objective multivariate methods. Bio-geoclimatic datasets were analysed using cluster analysis techniques to define biogeographical units. A georeferenced floristic database for Algerian strict-endemic plants was compiled, including distribution information from different sources, to characterise the indicator species of these units. Our new proposal for Algeria encompasses 28 biogeographical units recognised within the country that reflect specific regional topography and ecoclimatic conditions. Eight distinct and spatially coherent sectors were identified, and 20 nested districts were detected, based on biogeographical features. All of these biogeographical units are listed and their position and boundaries are mapped. The main predictive environmental descriptors of the sectors were Thornthwaite aridity index, elevation, Min Temperature of Coldest Month (Bio6), Precipitation of Warmest Quarter (Bio18), Coefficient of variation of Enhanced Vegetation Index (EVI), Evenness of EVI, and soil organic carbon. We highlighted the endemic plants that define the districts, using the indicator species criterium. The use of a large dataset of environmental factors and endemic plant species, coupled with numerical analyses, makes this study novel and allows an enhanced bioregionalization system for Algeria. We provide a reliable sectorisation for use in conservation planning, biodiversity assessment, or climate change studies.